2019
DOI: 10.30596/bibliocouns.v2i3.3736
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Assertive Training Techniques and Thought-Stopping Techniques to Increase Student Assertiveness Ability

Abstract: In carrying out activities, not all individuals/students can behave assertively and instead choose to act non-assertive (passive), such as harboring feelings, pretending, holding differences of opinion, or vice versa by being aggressive. Allowing yourself to be non-assertive can threaten the relationship because one party will feel used by the other party, not resolve the emotional problems they face, and can cause anxiety and stress. The purpose of this study is to examine the group counseling techniques asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
6
2
1
Order By: Relevance
“…Furthermore, other research also found that when an individual can see and realize all aspects that occur from various perspectives, he can receive experiences from the past and even the present, so he can accept himself as he is (Bulantika & Sari, 2019). Furthermore, the dimension of mindfulness trait that significantly affects the self-acceptance dimension is the describing dimension.…”
Section: Finding and Discussionmentioning
confidence: 97%
“…Furthermore, other research also found that when an individual can see and realize all aspects that occur from various perspectives, he can receive experiences from the past and even the present, so he can accept himself as he is (Bulantika & Sari, 2019). Furthermore, the dimension of mindfulness trait that significantly affects the self-acceptance dimension is the describing dimension.…”
Section: Finding and Discussionmentioning
confidence: 97%
“…", saat mengalami pemikiran negatif berulang, tidak dan distorted. Kemudian mengganti pikiran negatif tersebut dengan pikiran lain yang lebih positif dan realistis (Bulantika & Sari, 2019).…”
Section: B Pembahasanunclassified
“…Academic ability is the scientific foundation of tips for implementing professional guidance and counseling services (Bulantika & Sari, 2019). Academic competence is the foundation for the development of professional expertise, which includes: (1) profoundly understanding the counselee being served, (2) mastering the foundation and theoretical framework of guidance and counseling, (3) providing guidance and counseling services that are independent, and (4) developing personal and professional counselor on an ongoing basis.…”
Section: Counselor Competenciesmentioning
confidence: 99%